Numerical parameter study on lubricant evolution in heat assisted magnetic recording (HAMR) system - Shahindra Mohamed Shah. (2012)
This report contains numerical simulation, adopting the finite volume method, to investigate the heat transfer and the depletion of lubricant in the heat assisted magnetic recording (HAMR) system. The setup of the system is in such a way that a laser beam mechanism is mounted on a flying slider head which is positioned above the surface of a rotating disk. The disk is coated with a thin film of lubricant material.